Impact of a Structured Response and Evidence-Based Checklist on In-hospital Stroke Outcomes. Issue 3 (June 2020) - Snavely, Joshua; Thompson, Hilaire; Bridges, Elizabeth; Fathi, Joelle
ABSTRACT: BACKGROUND: In-hospital stroke events account for 2% to 17% of all ischemic strokes in the United States. Current stroke guidelines do not provide guidance on how to care for in-hospital stroke. Use of checklists during high-acuity events reduces error and provides clarity for responding staff. We sought to determine whether the use of an evidence-based checklist to guide in-hospital stroke response improved intervention times and patient outcomes. METHODS: This study used a retrospective chart review of patients hospitalized between January 1, 2016, and December 31, 2018, at a community hospital certified as a primary stroke center with the Joint Commission. Encounters were sorted into preintervention and postintervention groups to evaluate for change in treatment rates, new or worsened disability, and mortality. Nursing staff who respond to in-hospital stroke calls ("response staff") were also surveyed regarding their perception of benefit and firsthand experience when using the checklist. RESULTS: A total of 168 patient charts were reviewed (18 prechecklist, 150 postchecklist). After checklist implementation, treatment with intravenous thrombolytics for in-hospital stroke events increased from 0% to 11%. All-cause mortality decreased from 23.1% to 15.0%, whereas ambulatory disability at discharge increased from 38.0% to 62.1%. The increase in disability likely reflects the reduction in mortality, improved data collection, and the increase in postimplementation reporting. CONCLUSIONS: Use of a checklist during inpatient stroke events can potentially increase adherence to guidelines for appropriate treatment and reduce mortality. Hospital response teams should consider use of a structured response system with an evidence-based checklist for high-acuity, low-frequency events such as in-hospital stroke. Abstract : Supplemental digital content is available in the text.